Pengaruh Insentif dan Motivasi Kerja terhadap Semangat Kerja Karyawan pada SMKS YKPP Bontang - Nur Azizah, Fitriani; Ashari, Enil; Kiswanto, Heri (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to investigate the influence of incentives and work motivation on employee morale at SMKS YKPP Bontang, with the hope of providing insight into human resource (HR) development strategies in educational institutions. This research uses quantitative methods by applying multiple linear regression analysis to investigate the influence of incentives and work motivation on employee morale at SMKS YKPP Bontang. The results of this research show that incentives and work motivation have a positive and significant influence on employee morale at SMKS YKPP Bontang. This indicates that increasing incentives and motivation can effectively increase work morale, which in turn can contribute to improving employee performance and the quality of education at the institution. The novelty of this research lies in its focus on the influence of incentives and work motivation on employee morale in educational institutions, especially at SMKS YKPP Bontang. While many studies have explored the relationship between incentives, motivation, and morale in various sectors, this research specifically identifies and analyzes the factors that influence morale in the context of technical and vocational education